Burnout subtypes in the German working population: Differentiation by symptomatology, work-related factors and structural impairment according to the OPD - Julia Perlinger; Johannes C. Ehrenthal; Christiane Montag; Thomas Kretschmar (PLoS ONE, 2026)
Farber’s typological approach expands burnout models by identifying three burnout subtypes: frenetic, underchallenged, and worn-out. Despite its potential, research on this approach is limited, especially in the German working population. This study translated and validated the Burnout Questionnaire for Clinical Subtypes (BCSQ-12) into German and examined these burnout subtypes in the German working population. Using a non-probabilistic online quota sampling method, 616 employees were surveyed. The BCSQ-12 was translated and evaluated for its psychometric properties (EFA, Varimax rotation). Burnout subtypes were identified through hierarchical and K-means cluster analysis and analysed for symptomatologic, work-related and individual differences, particularly structural impairment (ANOVA). Additional questionnaires assessed burnout (MBI-GS-D), depression (PHQ-9), work engagement (UWES-9), job demands (COPSOQ), social support (MSPSS), and structural impairment (OPD-SQ). The BCSQ-12 demonstrated satisfactory psychometric properties and confirmed its three-factor structure. The cluster analyses revealed four profiles: non-burned-out, frenetic, underchallenged and worn-out, which differed in terms of the symptomatologic, work-related and individual factors. The pattern of resources and demands between the burnout subtypes indicates a deterioration from the frenetic to the underchallenged to the worn-out employee. The present results emphasize possible advantages of including burnout profiles into the general assessment of burnout and indicate the need for tailored interventions.